Faktor-Faktor Yang Mempengaruhi Integritas Laporan Keuangan: Audit Tenure, Struktur Corporate Governance Dan Ukuran KAP - Nala Ratih; Cris Kuntadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this research is to obtain empirical evidence regarding the influence of audit tenure, governance structure (institutional ownership, management ownership, audit committee, independent commissioner) and KAP size on the integrity of financial reports of Indonesian manufacturing companies. Financial report integrity is defined as the extent to which financial reports present correct and fair information. The independent variables used in this research are audit offices, management structures which are analyzed based on institutional ownership, management ownership, audit committee, independent commissioners, and KAP measures for financial reporting integrity. The dependent variable used in this research is the integrity of financial reports which were analyzed conservatively in the reference year 2007-2009. The research sample is manufacturing companies listed on the Indonesia Stock Exchange (BEI) from 2007 to 2009. Data will be collected using the convenience sampling method . A total of 105 companies were selected as samples. The analytical method for this research uses logistic regression. The results of the research show that the management structure of a company (institutional ownership, management ownership, audit committee, independent commissioner) and the size of the KAP have a significant effect on the integrity of financial reports. However, audit duration does not have a significant influence on the integrity of financial statements.